Comparing MRI metrics to quantify white matter microstructural damage in multiple sclerosis. Issue 10 (19th March 2019) - Lipp, Ilona; Jones, Derek K.; Bells, Sonya; Sgarlata, Eleonora; Foster, Catherine; Stickland, Rachael; Davidson, Alison E.; Tallantyre, Emma C.; Robertson, Neil P.; Wise, Richard G.; Tomassini, Valentina
Abstract: Quantifying white matter damage in vivo is becoming increasingly important for investigating the effects of neuroprotective and repair strategies in multiple sclerosis (MS). While various approaches are available, the relationship between MRI‐based metrics of white matter microstructure in the disease, that is, to what extent the metrics provide complementary versus redundant information, remains largely unexplored. We obtained four microstructural metrics from 123 MS patients: fractional anisotropy (FA), radial diffusivity (RD), myelin water fraction (MWF), and magnetisation transfer ratio (MTR). Coregistration of maps of these four indices allowed quantification of microstructural damage through voxel‐wise damage scores relative to healthy tissue, as assessed in a group of 27 controls. We considered three white matter tissue‐states, which were expected to vary in microstructural damage: normal appearing white matter ( NAWM ), T2‐weighted hyperintense lesional tissue without T1‐weighted hypointensity ( T2L ), and T1‐weighted hypointense lesional tissue with corresponding T2‐weighted hyperintensity ( T1L ). All MRI indices suggested significant damage in all three tissue‐states, the greatest damage being in T1L . The correlations between indices ranged from r  = 0.18 to r  = 0.87. MWF was most sensitive when differentiating T2L from NAWM, while MTR was most sensitive when differentiating T1L from NAWM and from T2L . Combining the four metrics into one, through a principal component analysis, did not yield a measure more sensitive to damage than any single measure. Our findings suggest that the metrics are (at least partially) correlated with each other, but sensitive to the different aspects of pathology. Leveraging these differences could be beneficial in clinical trials testing the effects of therapeutic interventions.